Analysis Of The Influence Of Integrated Vertical Organizational Communication And Leadership Style Of School Principal On Organizational Communication In School - Slamet Riyadi; Akhmad Ramli; Zahra Khusnul Lathifah; Muhamad Rif'an; Heri Kurniawan (Journal on Education, 2024)
In order to create an organizational communication climate, this research seeks to identify leadership philosophies and organizational communication patterns. A post-positivistic paradigm was employed in this study. A case study methodology was employed in this investigation. Purposive sampling was the method employed in this study. Pattern matching is the method of data analysis applied in this study. The study revealed that the school has successfully adopted an organizational communication strategy by using a high-quality communication pattern. This approach is supported by several open and seamless organizational communication channels, including horizontal, upward, diagonal, and downward communication. Apart from that, the organizational culture implemented also supports smooth communication within the division. The leadership style applied is also a combination of democratic, transactional, and transformational leadership styles. The organizational communication climate established at the school has also proven to be supportive, facilitating open, smooth, and honest communication between various levels and divisions in the school. This contributes to improving the quality of work and comfort of interaction for division members.